Energy-Spreading-Transform Based MIMO Systems: Iterative Equalization, Evolution Analysis, and Precoder Optimization - Yuan, Xiaojun; Ma, Junjie; Ping, Li (IEEE transactions on wireless communications, 2014)
In this paper, we develop a novel iterative equalization algorithm for energy-spreading-transform (EST) based multiple-input multiple-output (MIMO) systems. We show that the proposed scheme significantly outperforms the existing non-linear MIMO equalizers in various system setups. We further investigate the precoder design based on the signal-to-interference-plus-noise-ratio (SINR) variance evolution technique, so as to exploit the available channel state information at the transmitter (CSIT). We derive the optimal precoding directions, and show that the precoder optimization then boils down to a simple power allocation problem that is solvable using convex programming. Numerical results demonstrate that the optimized precoder can achieve a significant power gain, as compared with the non-optimized scheme.